Single-Longitude-Mode Fiber Laser Implementation by Using Only Two Subring Cavities in Serial/Parallel Connection. Issue 4 (4th July 2019) - Lee, Hsin-Che; Lee, Yin-Wen; Chang, Jiun-Shin; Liaw, Shien-Kuei
ABSTRACT: By incorporating double-ring cavities and a piece of un-pumped Er 3+ -doped fiber (EDF) as a saturable absorber, we report a single-longitude-mode EDF fiber laser at C-band. The single-longitude-mode is obtained, the first time, by inserting only two subring cavities in either serial connection or parallel connection. The fiber laser has an optical signal-to-noise-ratio of 34.5 dB and a maximum power fluctuation of less than 1.3% for 1-hr operation. It was then modulated up to 10 Gbit/s by using an electro-optic modulator for eye diagrams, compared to back-to-back transmission. Such a compact and low-cost fiber laser is potential for high-speed optical communication.